Modeling and Simulation of a Three-Phase Induction Motor Under Open-Phase Fault - Zaimen, Hicham; Rezig, Ali; Touati, Said (International Conference on Emerging and Renewable Energy: Generation and Automation,ICEREGA’19, Istanbul, Turkey, 2019)
This paper discusses a contribution to the modeling of a three-phase induction motor with one of its stator phases,open. The dynamic behavior of motor for different operation modes (healthy and faulty) will be studied by using the equivalent two-phase d-q model referenced to the stationary reference frame. All results of this work were obtained using the MATLAB software.